THE CONTENT-ESSENCE OF THE UNDERSTANDING OF “TIME” AND THE HISTORY OF ITS ORGANIZATION - Sultanova, Shokhista (Журнал иностранных языков и лингвистики, 2023)
This article examines the content-essence of the understanding of “time” and the history of its organization. Several works of scientists on this topic have been investigated. The views of various scholars on the concept have been cited as examples.